Peran Kemitraan Agribisnis Koperasi Eptilu dalam Mendukung Pemberdayaan Petani di Kabupaten Garut Jawa Barat - Putra, Rizki Aditya; Martina, Martina; Kurniasih, Dedeh; Hutahaean, Chryst Richet; Vera, Konselia D (LPPM Universitas Malikussaleh - Indonesia, 2025)
Farmers often face challenges in accessing capital, technology, and markets, which hinder their welfare improvement, thus requiring farmer empowerment. Agricultural cooperatives, such as Koperasi Eptilu in Garut Regency, are expected to serve as business partnership institutions capable of implementing farmer empowerment. This study aims to analyze the role of Koperasi Eptilu in addressing these issues, particularly in empowering small farmers. The method used is a case study with a descriptive qualitative approach, involving in-depth interviews with cooperative managers and partner farmers. The results of the study show that this cooperative has successfully reduced farmers' dependence on middlemen, increased farmers' bargaining power in the market, and provided price guarantees and broader market access. Koperasi Eptilu also plays a role in risk management, such as price fluctuations and extreme weather. Koperasi Eptilu has successfully empowered small farmers with a sustainable and collaborative approach, strengthening the local economy and supporting food security.